Visual workplace visual thinking creating enterprise excellence through the technologies of the visual workplace - Galsworth, G. D. (CRC Press, Taylor & Francis Group, 2017)
Visual Workplace/Visual Thinking (VWVT) was written by the acknowledged leading expert in workplace visuality. With over 25 full-color albums of visual solutions, 50+ graphs and charts, a detailed table of contents and in-depth Index, this 277-page book positions the technologies of the visual workplace as a premier improvement strategy on every company's journey to operational excellence.